Mengulik Implementasi Kebijakan Pemerintah Mengenai Pengesahan Perppu Cipta Kerja: (Studi Pada Pekerja, Serikat Pekerja dan Perusahaan di Kota Semarang) - Muhammad Stalastul Mustofa; Sijabat, Rauly; Meiriyanti, Rita (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2024)
This research aims to analyze the implementation of government policies regarding the ratification of the Job Creation Perppu for workers, trade unions and companies in the city of Semarang. The benefit of this research is that this research can be used as input in preparing and determining appropriate Human Resource Management strategies in order to get more optimal results. The partners and informants for this research are workers, unions and companies in the city of Semarang. Data analysis in this research used qualitative interview research. The results of the analysis and discussion show that the main objective of the PERPPU policy regarding job creation is to create jobs through increasing the ease and security of doing business, increasing investment, and protecting and empowering workers (KKIR). The impact of PERPPU implementation on employees is that many employees are laid off, employees receive severance pay. low, permanent employees are replaced with contract or social workers, and employees feel uncertain about employee welfare. The impact of PERPPU implementation on the company is that company regulations become more structured with the PERPPU being ratified. The company feels that it is fair with employee welfare and company profits. Impact of implementation. PERPPU on work unions. Work unions are experiencing outsourcing contracts at the same time, BPJS is not paying enough attention to leave, wages below the UMK are not being paid attention to, they are not getting any protection at all.